IMPACT OF LEVERAGE AND PROFITABILITY ON FIRM VALUE WITH FINANCIAL DISTRESS AS A MEDIATING VARIABLE - Billikusuma, Christoforus Axel; Saputro, Stefanus Dimas Ryan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The purpose of this study is to look at how profitability and leverage affect a company's value, as well as how financial crisis affects manufacturing enterprises that are listed on the Indonesia Stock Exchange. This study employs purposive sampling to choose samples from the manufacturing industry sector between 2019 and 2022, with a focus on the sector as a whole. The data collection comprises 67 firms' financial data. Empirical evidence indicates that leverage exerts a detrimental impact on financial distress, but profitability positively influences financial hardship. The value of a corporation is negatively impacted by financial challenges, profitability, and leverage. Leverage and Profitability Increase Company Value, with Financial Distress acting as a moderating element. By taking anticipated risks into account, this research attempts to use corporate value as a foundation for investing. It is envisaged that investors would make enormous returns from this venture. It is intended that the research results would serve as a resource and answer for anyone looking to fund a business. Additionally, a clearer comprehension of the connection between financial difficulty and firm valuation may be obtained from this research. Furthermore, these results might serve as a guide to comprehend the moderating influence of leverage and profitability on the valuation of companies.